This Recession Is Wearing Me Out! Health-Related Quality of Life and Economic Downturns - Davalos, Maria E. (2012)
Previous research on the relationships between macroeconomic conditions and health status reveal improvements in physical health during economic downturns. However, few studies have examined whether mental health status improves or declines during tough economic times. This paper estimates the effect of a key macroeconomic indicator, the state-level unemployment rate, on health-related quality of life. Analyzing recent data from Waves 1 and 2 of the NESARC and controlling for individual heterogeneity with fixed-effects models, our study suggests that health-related quality of life, both physical and mental, worsens with increases in the unemployment rate. Although the effect sizes are relatively small in magnitude for both outcomes, the impact is more pronounced for mental health. These results raise questions about the unexpected findings reported in earlier studies of a health-improving effect of economic downturns and suggest that the current worldwide economic recession may have some serious hidden costs.